Appropriating Epistemic Norms of Science through Sustained Practice with Argumentation: Can It Happen? A Learning Progressions Perspective - Mehmet Aydeniz; Kader Bilican (Journal of Education in Science, Environment and Health)
The purpose of this study was to explore the effect of sustained practice with argumentation on the quality of students’ written arguments. Participants consisted of 37 students; 22 males and 15 females enrolled in a 6th grade middle school classroom. Students completed six argumentation tasks but only four of them were considered for data analyses as the first two tasks were used to get the students familiar with the language and structure of argumentation. Data were analyzed using the Claim, Evidence and Reasoning (CER) Framework. Findings reveal several patterns regarding students’ use of claim, evidence, and reasoning across 4 tasks that were subject to our evaluation. First, there was not a consistent pattern of improvement in students’ use of evidence. Second, there were not any consistent improvements in students’ use of reasoning across four tasks. Our discussion focuses on the role of context, content knowledge and teacher framing in the quality of arguments developed by students.